2014
DOI: 10.1016/j.neuropsychologia.2014.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic changes in network activations characterize early learning of a natural language

Abstract: Those who are initially exposed to an unfamiliar language have difficulty separating running speech into individual words, but over time will recognize both words and the grammatical structure of the language. Behavioral studies have used artificial languages to demonstrate that humans are sensitive to distributional information in language input, and can use this information to discover the structure of that language. This is done without direct instruction and learning occurs over the course of minutes rathe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(31 citation statements)
references
References 63 publications
(71 reference statements)
7
24
0
Order By: Relevance
“…The initial phase of learning may be characterized by different cognitive strategies than employed at even slightly later times during the learning process, when the learner has begun to accumulate experience with a language corpus. This was demonstrated in a recent natural-language study of Icelandic sentence forms (Plante, Patterson, Dailey, Almryde, & Fridriksson, 2014). This study demonstrated that patterns of activation can be highly dynamic with learning, even within the initial 10 minutes of exposure to a new language.…”
Section: Introductionmentioning
confidence: 68%
See 3 more Smart Citations
“…The initial phase of learning may be characterized by different cognitive strategies than employed at even slightly later times during the learning process, when the learner has begun to accumulate experience with a language corpus. This was demonstrated in a recent natural-language study of Icelandic sentence forms (Plante, Patterson, Dailey, Almryde, & Fridriksson, 2014). This study demonstrated that patterns of activation can be highly dynamic with learning, even within the initial 10 minutes of exposure to a new language.…”
Section: Introductionmentioning
confidence: 68%
“…Indeed, information-rich input may promote the recruitment of a neural network that is quite extensive, and highly dynamic over time (cf. Plante et al, 2014). Furthermore, because use of statistical information has resulted in rapid learning of words in prior artificial language studies, learners provided with input in which transitional probabilities predict word boundaries should show better learning than those provided with low predictability input.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…During auditory SL, the superior temporal gyrus-a region implicated in auditory perception, speech processing and forward speech prediction [52][53][54]-activates differentially to statistically predictable versus unpredictable transitions [55][56][57][58]. Auditory SL also activates the inferior frontal gyrus during test performance [55] and online learning of novel sequential structure [59] with some indication that this region may reflect recognition of accumulated statistical information [55,59]. There is also evidence that cortical regions activate to speech in three month olds [60].…”
Section: Candidate Memory Systems For Statistical Learningmentioning
confidence: 99%